Methodological Approaches to the Diagnosis and Forecast of the Long-Wave Fluctuations in the Economy - Safiullin, Marat Rashitovich; Elshin, Leonid Alekseevich; Nikiforova, Elvira Gumarovna (International Journal of Economics and Financial Issues, 2016)
Evolutionary development of economic systems demonstrates the cyclical nature in time. In such a case these cyclical fluctuations comprise all facets of economic relations, starting from the production sector and ending the sphere of services, focused on ensuring the interaction effectiveness of economic relations. As the modern world experience shows the cyclical dynamics has a number of its individual features depending on a wide range of factors, such as the type of economic system (planned or market), market type, forms and methods of state or other effects on the regulation of cycles within smoothing process, etc. The knowledge of these factors, the nature of their origin and the impact on the long-term cyclical fluctuations is not a trivial matter and requires a comprehensive system analysis, based on a synthesis and a dialectic of the established approaches. Keywords: long-term cycles, phase shifts, advanced development cycles, technological modes. JEL Classifications: Ð¡10, C53, E37, F17, O10